PENERAPAN LATIHAN MOTORIK HALUS UNTUK MENINGKATKAN KEMAMPUAN MENULIS HURUF SISWA TUNAGRAHITA KELAS DASAR III DI SLB. NEGERI 2 MAKASSAR - Rahman, Abdul (JURNAL NALAR PENDIDIKAN, 2020)
The aims of this study were to find out the writing ability and writing activeness of Elementary Class III tunagrahita students at SLB Negeri 2 Makassar through the application of fine motor training. This study used a classroom action research. The research subjects were two students with tunagrahita in Elementary Class III SLB Negeri 2 Makassar with data collection through test, documentation, and observation. Data analysis was performed by using descriptive-qualitative and quantitative analysis technique. The results showed that the ability to write letters of the Elementary Class III tunagrahita students at SLB Negeri 2 Makassar with the application of the fine motor training had a significant increase qualitatively from cycle I to cycle II. The application of this fine motor training showed the better result from cycle I to cycle II. The increase of student activities included the overall activities given to the students.Â Keywords: Fine Motoric, Writing Letters, Tunagrahita